2018
DOI: 10.1590/0366-69132018643692267
|View full text |Cite
|
Sign up to set email alerts
|

Influência dos cátions lítio (Li + ), sódio (Na + ) e potássio (K + ) na reologia de bentonitas brasileiras para uso em fluidos de perfuração base aquosa

Abstract: ResumoOs cátions lítio (Li + ), sódio (Na + ) e potássio (K + ) encontram-se em primeiro lugar no plano de seletividade para a obtenção de bentonitas monocatiônicas a partir das policatiônicas, influenciando de forma específica o comportamento reológico dos fluidos de perfuração base água. O objetivo deste trabalho foi estudar a influência do Li + , Na + e K + na reologia de bentonitas do estado da Paraíba, Brasil, para uso em fluidos de perfuração à base de água. Os novos depósitos de bentonitas brasileiras f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
2
10
0
1
Order By: Relevance
“…Table I presents the results of the chemical composition of the polycationic and monocationic (additive) samples A, B, C and D. It was observed that the results obtained presented SiO 2 contents in the range of 47%-51% and 18%-22% Al 2 O 3 , from the tetrahedral and octahedral sheets; 6%-8% Fe 2 O 3 and 2%-3% MgO, resulting from isomorphic substitutions occurring in the octahedral sheet; 3%-4% Na 2 O due to the process of additivation with the carbonate Na 2 CO 3 ; 1%-6% CaO and 0-1% K 2 O, among other oxides, where CaO was significant in samples B and D, confirming the results of XRD (Fig. 1), since different location extraction resulted in different chemical compositions [2,6]. The results presented are typical of the clays of the State of Paraíba [2,[6][7][8].…”
Section: Materials and Methodologysupporting
confidence: 77%
See 4 more Smart Citations
“…Table I presents the results of the chemical composition of the polycationic and monocationic (additive) samples A, B, C and D. It was observed that the results obtained presented SiO 2 contents in the range of 47%-51% and 18%-22% Al 2 O 3 , from the tetrahedral and octahedral sheets; 6%-8% Fe 2 O 3 and 2%-3% MgO, resulting from isomorphic substitutions occurring in the octahedral sheet; 3%-4% Na 2 O due to the process of additivation with the carbonate Na 2 CO 3 ; 1%-6% CaO and 0-1% K 2 O, among other oxides, where CaO was significant in samples B and D, confirming the results of XRD (Fig. 1), since different location extraction resulted in different chemical compositions [2,6]. The results presented are typical of the clays of the State of Paraíba [2,[6][7][8].…”
Section: Materials and Methodologysupporting
confidence: 77%
“…Using the mass of the sample (dry clay) used, the mass of sodium carbonate required to add to the clay was calculated [6]. Water was then added so that an ideal humidity of 30%-40% was reached and placed in closed bags during 5 days for curing so that the additive process was effective [2,6]. After the curing period, the rheological and filtration behaviors were studied.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 3 more Smart Citations